Epidemiology and associated factors for hospitalization related respiratory syncytial virus infection among children less than 5 years of age in Northern Thailand - Wilawan Chaiut; Ratana Sapbamrer; Sauwaluk Dacha; Tavitiya Sudjaritruk; Rungnapa Malasao (Elsevier, 2023)
Background: Respiratory syncytial virus (RSV) is often the main problem in young children that require hospitalization. The objective of this study was to identify factors associated with RSV-related hospitalizations in young children less than five years old. Methodology: A retrospective study was conducted for acute respiratory tract infection (ARTI) at a tertiary care hospital from January 2017 to December 2021 by using binary logistic regression analysis to detect the associated factors with RSV-related hospitalizations in children. Results: RSV-related hospitalization was detected in 293 of 410 (71.46 %) cases of RSV infection, most of which appeared in the rainy months of August to November. The most common symptoms and signs were 81.5 % rhinorrhea, 70.7 % cough, 68.5 % sore throat, 68.3 % sputum production, and 66.8 % fever. Factors associated with RSV-related hospitalization were age less than or equal to 2 years (aOR = 4.62, 95 % CI = 1.86-11.44), preterm birth (aOR = 2.61, 95 % CI = 1.05-6.10), patients with underlying disease (aOR = 3.06, 95 % CI = 1.21-10.34), and the presenting symptoms with sputum production (aOR = 16.49, 95 % CI = 3.80-71.55). Laboratory blood tests, low levels of hematocrit (aOR = 9.61, 95 % CI = 1.09-84.49) was the associated factor for hospitalization with RSV infection (p < 0.05). Conclusions: Factors associated with RSV-related hospitalizations in children were age less than or equal to two years, preterm birth, underlying disease, symptoms of sputum production. The low level of hematocrit was also associated with RSV-related hospitalizations in these children.